Differences Between Bulgarian Family and Non-family Businesses: A Multivariate Logit Approach - Yordanova, Desislava I. (International Review of Management and Marketing, 2016)
There is a lack of understanding about differences between family and non-family businesses operating in the transition economies in Central andEastern Europebecause the available research has focused mainly on other contexts. The present research explores differences between family and non-family firms in a sample from a Central and Eastern European country. The proposed hypotheses are guided by previous theoretical and comparative empirical research on family business. In response to the methodological concerns expressed in the literature about the methodological appropriateness of some comparative studies of family and non-family businesses, this study utilizes multivariate logit regression that controls for the effects of a number of contextual variables. This approach allows for detecting real rather than sample differences between the studied family and non-family businesses. The empirical findings demonstrate the presence of both similarities and differences between the studied family and non-family businesses. The paper provides recommendations for future research. Keywords: Differences, family businesses, non-family businesses, Central andEastern Europe. JEL Classification: M19